ARTIFICIAL INTELLIGENCE AND GLOBAL SOCIETY - Islombek Abdulakhatov (Academia Science Repository, 2023)
The rapid development of information technologies led to a battle be-tween machine intelligence and human intelligence, and today’s trend shows that machines will likely surpass human intelligence in the near future. Starting from the economic sector to the healthcare sector, artificial intelligence can transform our lives in almost every area. Information technology has a high market space in all countries and has become the top priority in the fields of infrastructure construction, electronic governance, education, software development, and manufacturing. This article attempts to cover areas where AI may have positive or negative consequences, the advantages, and disadvantages of integration of AI, techno-logical unemployment, and questions and doubts about AI.